The Effect of Audit Quality on Corporate Governance Mechanism and Financial Reporting - Akpovwre Eyenubo, Samuel; Abdul Hamid, Mohamad Ali; Mohammed, Mudzamir (Opción, 2019)
This paper examines the impact of audit quality on corporate governance mechanism and financial reporting quality in Nigeria. Descriptive and panel data analysis are utilized. The results of the descriptive statistics show that financial reporting quality is low in Nigeria compared to developed economies. The panel regressions reveal that ownership structure, block holders and director shareholder in the company positively influence financial reporting quality. In conclusion, the study revealed that audit quality affected the viability of corporate governance audit committee variables in improving the FRQ of firms in Nigeria.